IMPLEMENTASI BIMBINGAN KONSELING DALAM PEMBINAAN AKHLAK PESERTA DIDIK PONDOK PESANTREN MASDARUL ULUM OGAN ILIR - Ediansyah (UNISAN JURNAL, 2023)
Implementation of counseling guidance in fostering student morals is an educational process that focuses on changing the morals and behavior of students to behave well and have good morals. The implementation of counseling guidance in moral development for students at the Masdarul Ulum Islamic Boarding School Teluk Kecapi Pemulutan Ogan Ilir South Sumatra has been carried out well. Guidance and Counseling is an integral activity that cannot be separated. The word Guidance (Guidance) is always coupled with Counseling as a compound word, Counseling which is one of the Guidance techniques is often said to be the core of all services and Guidance. Methods of data collection is done by using the method of observation, interviews and documentation. In the analysis carried out the steps of data reduction, data presentation and drawing conclusions. As for analyzing by way of inductive thinking. Based on the data obtained, the results of the research on the Implementation of Counseling Guidance in the Moral Development of Students at the Masdarul Ulum Islamic Boarding School Teluk Kecapi Pemulutan Ogan Ilir South Sumatra show a fairly good and significant level of change, it can be seen from the students always following counseling guidance and good moral development. using the method of understanding, advice, motivation, encouragement and habituation. So that slowly can change the nature and habits of students for the better.